Current Smoking Does Not Modify the Treatment Effect of Intravenous Thrombolysis in Acute Ischemic Stroke Patients—A Post-hoc Analysis of the WAKE-UP Trial - Schlemm, Ludwig; Kufner, Anna; Boutitie, Florent; Nave, Alexander Heinrich; Gerloff, Christian; Thomalla, Götz; Simonsen, Claus Z.; Ford, Ian; Lemmens, Robin; Muir, Keith W.; Nighoghossian, Norbert; Pedraza, Salvador; et al. (Frontiers in Neurology, 2019)
Background: The ‘smoking paradox’ indicates that patients with acute ischemic stroke (AIS) who smoke at the time of their stroke may have a better prognosis after intravenous thrombolysis than non-smokers. However, findings are inconsistent and data analyzing the effect of smoking on treatment efficacy of intravenous thrombolysis are scarce. Methods: We performed a pre-specified post-hoc subgroup analysis of the Efficacy and Safety of MRI-Based Thrombolysis in Wake-Up Stroke (WAKE-UP) trial that randomized AIS patients with unknown time of symptom onset who had diffusion-weighted imaging-fluid attenuation inversion recovery (DWI-FLAIR) mismatch to either alteplase or placebo. Patients were categorized as current smokers or non-smokers (including former smokers and never-smokers). Baseline demographic and clinical characteristics, as well as clinical and imaging follow-up data were analyzed according to smoking status. Results: 486 patients were included in the analysis. Current smokers (133, 27.4%) were younger (60.1±13.0 vs 67.2±10.3 years; p<0.001) and less often had arterial hypertension (45.0% vs 56.8%; p=0.02) or atrial fibrillation (3.8% vs 15.3%; p<0.001). The acute stroke presentation was more often due to large vessel occlusion among current smokers (27.1 vs. 16.2%; p=0.01), and smokers had a trend towards more severe strokes (National Institutes of Health Stroke Scale score>10 in 27.1% vs 19.5%; p=0.08). The treatment effect of alteplase, quantified as odds ratio for a favorable outcome (modified Rankin Scale [mRS] score at 90 days of 0 or 1), did not differ between current smokers and non-smokers (p-value for interaction: 0.59). After adjustment for age and stroke severity, neither the proportion of patients with favorable outcome, nor the median mRS score at 90 days differed between current smokers and non-smokers. When additional potential confounders were included in the model, the median mRS score was higher in current smokers than in non-smokers (cOR of better outcome for current smokers vs non-smokers: 0.664 [0.451 – 0.978], p = 0.04). Conclusions: In patients with mild to moderate MRI-proven AIS and unknown time of symptom onset with DWI-FLAIR mismatch, current smokers had worse functional outcome as compared to non-smokers. Current smoking did not modify the treatment effect of alteplase.